A Novel NAC Transcription Factor From Eucalyptus, EgNAC141, Positively Regulates Lignin Biosynthesis and Increases Lignin Deposition - Sun, YiMing; Jiang, Chunxue; Jiang, Ruiqi; Wang, Fengying; Zhang, Zhenguo; Zeng, Jianjun (Frontiers in Plant Science, 2021)
Wood formation is a complicated process under the control of large set of multi-level transcription factors. NAC transcription factor executed as “master switch” in this process by. However, a very limited members have been cloned and characterized in Eucalyptus, one of the most important economic woody plants. Here, we reported a NAC transcription factor form Eucalyptus grandis, EgNAC141, which have no homologues in Arabidopsis. EgNAC141 dominantly expressed in lignin-rich tissues, such as stem and xylem. Overexpression of EgNAC141 in Arabidopsis resulted in stronger lignification and broadened xylem party, as well as higher content of lignin. The expression of lignin biosynthetic genes in transgenic plants were significantly elevated compared with wild type plants. Transient expression of EgNAC141 specifically activated the expression of Arabidopsis lignin biosynthetic genes in dual-Luciferase assay. These results revealed that EgNAC141 is a positive regulator in lignin biosynthesis and the regulation mechanism of lignin biosynthesis is largely similar between woody and herbal plants.